Pengaruh Relaksasi Nafas Dalam Terhadap Penurunan Kecemasan Pasien Pre Operasi Di Instalasi Bedah Rsud Kabupaten Rejang Lebong Tahun 2025 - Maria Atvennia; Ice Rakizah Syafrie; Hengki Tranado (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Anxiety is a common psychological problem experienced by patients prior to surgery. High levels of anxiety can affect the patient's physiological condition and potentially worsen the surgical process. Deep breathing relaxation is a simple non-pharmacological intervention that can be used to reduce anxiety. This study aims to determine the effect of deep breathing relaxation on reducing anxiety in Pre-Operative Patients at RSUD Rejang Lebong Regency in 2025. This study used a quasi-experimental design with a one-group pre-test and post-test approach. The population consisted of 20 preoperative patients aged 17-50 years, selected using total sampling. The research instrument used APAIS questionnaire to assess anxiety. The intervention consisted of deep breathing relaxation techniques performed 4 hours before the patient entered the operating room and 1 hour before the patient entered the operating room. The deep breathing relaxation technique was administered for 15 minutes with breaks every 5 minutes. Data analysis was performed univariately for frequency distribution and bivariate using the Wilcoxon signed rank test. The results showed that before the deep breathing intervention, the majority of patients experienced mild anxiety (40%) and severe anxiety (35%). After the intervention, 40% of patients were in the non-anxious category, while severe anxiety decreased to 5% and no patients experienced panic. The Wilcoxon test results showed a Z value of -4.300 with P < 0.001, which means there is a significant difference between the anxiety levels before and after the intervention. The conclusion of this study is that deep breathing relaxation techniques are proven to be effective in reducing anxiety in preoperative patients. Nurses and patients are advised to apply deep breathing relaxation interventions as one of the efforts to reduce anxiety in preoperative patients.